AKIBAT HUKUM BAGI PIHAK YANG MENGUASAI HARTA WARISAN DALAM PERSPEKTIF HUKUM ISLAM - Virga Eka Pertiwi (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTInheritance is the transfer of ownership of property from a person who dies to someone who is still alive. In family life, it is possible for problems such as inheritance to occur. Inheritance often causes disputes because there are heirs who control greedily to own the entire inheritance without wanting to share it with other heirs. In addition, other factors that trigger inheritance disputes because the implementation of the distribution of inheritance in Indonesia is diverse, causing differences in the legal system that makes many people do not understand about inheritance law so that they often have misunderstandings.The type of research method used in this paper is mormative law research with a concentration on positive law inventory, legal principles and legal doctrine, legal discovery, legal systematics, synchronization and legal comparison.The legal consequences for the party who controls the inheritance without the approval of the other heirs to the detriment of the other heirs, are obliged to compensate materially or immaterially for the heirs who feel that their rights have been harmed due to violating the obligations as regulated in Article 175 paragraph 1 of the Legal Compilation. Islam and can be categorized as an unlawful act. Meanwhile, efforts that can be made by heirs who do not obtain inheritance because they have been controlled by other heirs are to conduct mediation first, but if they do not obtain a settlement agreement, then they may file an inheritance lawsuit to the Religious Court with the applicable terms and procedures.Keywords: Legal Consequences, Heirs, Inheritance, Islamic Law.